Efficacy and Safety of Autologous Follicular Unit Excision in Pediatric Secondary Cicatricial Alopecia: A Retrospective Case Series - Niu Y; Zhu L; Feng Y; Li Z; Zhang J; Jin Z; Ren C (Clinical, Cosmetic and Investigational Dermatology, 2025)
Yanchao Niu,1,* Ling Zhu,2,* Yanyan Feng,1 Zaibing Li,1 Jian Zhang,3 Zhoufeng Jin,4 Ci Ren3 1Department of Dermatovenereology, Chengdu Second People’s Hospital, Chengdu, Sichuan, People’s Republic of China; 2Medical Technology Department, Sichuan Nursing Vocational College, Chengdu, Sichuan, People’s Republic of China; 3Department of Dermatological Surgery, Shenyang Seventh People’s Hospital, Shenyang, Liaoning, People’s Republic of China; 4Department of Plastic Surgery, Shenyang Seventh People’s Hospital, Shenyang, Liaoning, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ci Ren, Department of Dermatological Surgery, Shenyang Seventh People’s Hospital, No. 13 Dongwei Road, Heping District, Shenyang, Liaoning, 110003, People’s Republic of China, Email renci7yuan@163.com Zhoufeng Jin, Plastic Surgery, Shenyang Seventh People’s Hospital, No. 13 Dongwei Road, Heping District, Shenyang, Liaoning, 110003, People’s Republic of China, Email 1978960974@qq.comObjective: To explore the efficacy of Follicular Unit Excision (FUE) in treating pediatric secondary cicatricial alopecia.Methods: We selected 11 cases of patients under 18 years old who underwent treatment for secondary cicatricial alopecia at the Chengdu Hengmei Hair Medical Clinic from January 1, 2021, to December 31, 2022. Among them, there was 1 female and 10 males. All patients underwent FUE procedures. After 12 months, the assessment of the surgical efficacy was evaluated using the Global Aesthetic Improvement Scale (GAIS), and the incidence of complications was recorded.Results: Among the 11 patients, none experienced complications such as infection, skin necrosis, significant hematoma, unnatural appearance, or temporary hair loss. 6 cases (54.5%) were rated as 1 on the GAIS, indicating extreme satisfaction. 2 cases (18.2%) were rated as 2, signifying satisfaction, resulting in an overall satisfaction rate of 72.7%. 1 case (9.1%) scored 3, showing limited improvement and dissatisfaction, and 2 cases (18.2%) scored 4, indicating no improvement.Conclusion: FUE hair transplantation is a safe, minimally invasive, and effective method for treating stable cicatricial alopecia in children, leading to significant aesthetic improvements for the patients. Further studies with larger cohorts are needed to confirm these results and explore long-term outcomes.Keywords: children, follicular unit excision, secondary cicatricial alopecia, global aesthetic improvement scale, GAIS